Black Medic Biology and Management in Turf - Barry J. Brecke; Ramon Leon; J. Bryan Unruh; Darcy E. P. Telenko (EDIS, 2014)
Black medic (Medicago lupulina) is a dark green annual with spreading, prostrate growth. Leaves are alternate with three leaflets on square stems. Leaflets are obovate to elliptic, toothed near the tip, and have a small spur on the tip. Bright yellow flowers are produced in tight, compressed clusters at leaf axils. Reproduction occurs via seed in tightly coiled black seed pods. This 2-page fact sheet was written by Barry J. Brecke, Ramon Leon, J. Bryan Unruh, and Darcy E. P. Telenko, and published by the UF Department of Environmental Horticulture, December 2013.